Education as Economic Investment: Comments on Tuition Fee Policy in Private Universities in Bangladesh - Haque, Wazedul; Islam, Kariul; Rahman, Mahmudur; Karmuzzaman, A. H. M.; Talukdar, Touhidul Islam; Miah, Sazib; Akter, Tuhin; Hossain, Alamgir; Tamzid, Mohammad; Hasan, Murad; et al. (Archives of Business Research, 2023)
Student fees for university programmes in Bangladesh have risen dramatically in recent years. This has been justified by the argument that such increases offer no economic disincentive to students seeking university admission. The present essay comments on that argument and finds several weaknesses in it. Fee increases may still be necessary, but this argument at least does not establish that they are innocuous.